2022
DOI: 10.1055/a-1793-9414
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of early gastric cancer with linked color imaging using an ultrathin endoscope: a video-based analysis

Abstract: Background and study aims Ultrathin endoscopy causes a minimal gag reflex and has minimal effects on cardiopulmonary function. Linked color imaging (LCI) is useful for detection of malignancies in the digestive tract. The aim of this study was to clarify whether LCI with ultrathin endoscopy facilitates detection of early gastric cancer (EGC) despite its lower resolution compared with high-resolution white light imaging (WLI) with standard endoscopy. Patients and methods This was a retrospective analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In such background mucosa, early detection of gastric cancer is difficult even for well-trained endoscopists, and EGCs are often missed during screening endoscopy using WLI alone [ 9 – 12 ]. Table 1 shows a summary of studies on LCI for the detection of gastric neoplasms [ 15 17 , 27 , 28 , 46 , 50 69 ]. To prepare Table 1 , we identified relevant studies in the literature by searching the databases of PubMed (Fig.…”
Section: Lci For Screening Of Egcmentioning
confidence: 99%
See 2 more Smart Citations
“…In such background mucosa, early detection of gastric cancer is difficult even for well-trained endoscopists, and EGCs are often missed during screening endoscopy using WLI alone [ 9 – 12 ]. Table 1 shows a summary of studies on LCI for the detection of gastric neoplasms [ 15 17 , 27 , 28 , 46 , 50 69 ]. To prepare Table 1 , we identified relevant studies in the literature by searching the databases of PubMed (Fig.…”
Section: Lci For Screening Of Egcmentioning
confidence: 99%
“…Non-experts placed the biopsy mark more accurately with LCI (82.3% vs. 87.2%, P < 0.001). Non-experts were indicated to prefer LCI over WLI Khurelbaatar et al [ 67 ] 2022 Retrospective/SC 508 EGCs from 456 patients Images of EGCs LCI significantly improved visibility of EGC regardless of differences in lesion morphology, histology, location, depth of invasion, and Hp status compared with conventional WLI Ishida et al [ 28 ] 2022 Retrospective/SC 99 EGC lesions from 88 patients Videos of EGCs and gastric mucosa captured using LED and laser endoscopy LED-WLI and LED-LCI can be used to visualize EGCs with non-inferiority to Laser-WLI and Laser-LCI Haruma et al [ 68 ] 2022 RCT/MC 1502 patients (patients with a history of gastrointestinal cancer) Real-time observation The detection rate of upper gastrointestinal neoplasms tended to be higher with LCI than with WLI among patients who underwent ultra-slim endoscopy Khurelbaatar et al [ 69 ] 2022 Retrospective/SC 52 EGCs and 29 nonmalignant lesions Video including cases of EGC or gastric atrophy alone using standard and ultra-thin endoscopies Ultra-thin LCI had a higher diagnostic sensitivity and significantly higher visibility scores and color difference than standard WLI SC single-center, MC multicenter, RCT randomized controlled trial, EGC early gastric cancer, IM intestinal metaplasia, LCI linked color imaging, WLI white-light imaging, BLI blue laser imaging, LED light-emitting diode, Hp Helicobacter pylori , M-Chromo-LCI magnifying linked color imaging with indigo carmine dye, M-BLI magnifying blue laser imaging, MR map-like redness, IC indigo carmine contrast method, CI confidence interval, AIM acetic acid indigo carmine mixture
Fig. 2 PRISMA 2009 flow diagram describing the selection of the studies included in our review
…”
Section: Lci For Screening Of Egcmentioning
confidence: 99%
See 1 more Smart Citation
“…The visibility of EGC by LCI using ultrathin endoscopes is superior to that by WLI using standard endoscopes with high resolution. Ultrathin endoscope (EG-L580NW) with LCI is also reported to have better sensitivity for EGCs than conventional endoscope (EG-L590WR) with WLI [24]. In the multicenter prospective trial, LCI is useful to identify neoplastic lesions for upper GI tract screening, even when used in ultrathin endoscopy [25].…”
Section: Painless Ultrathin Endoscopy As Screening Tool For Upper Gi ...mentioning
confidence: 99%
“…Consequently, the Japanese Guidelines for endoscopic diagnosis of gastric cancer state that the usefulness of IEE for the detection of early gastric cancer is under discussion (Evaluation by the modified Delphi method: 8, Strength of recommendation: None, Level of evidence: D) [ 72 ]. However, in comparison between LCI and WLI for detecting gastric cancer in a RCT, the percentage of patients with gastric tumours diagnosed in the first endoscopic examination was higher with LCI than with WLI [5.5% (41/750) vs. 3.3% (25/752), p = 0.011) and the proportion with overlooked neoplasms was lower in the LCI group than in the WLI group [ 5 ], suggested that LCI may be more effective than WLI for detecting gastric cancer [ 5 , 73 , 74 ]. Also, in a meta-analysis using reports investigated the usefulness of IEE (mostly NBI), the sensitivity and specificity for the diagnosis of intestinal metaplasia were 86 and 77%, and for dysplasia/early gastric cancer these values were 90 and 83%, respectively, and showed the usefulness of IEE for detection of gastric cancer [ 75 ].…”
Section: Usefulness Of Txi For Detecting Gastrointestinal Diseasesmentioning
confidence: 99%